2009
DOI: 10.1128/aem.01110-08
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Methicillin-Resistant Staphylococcus aureus Strains from Louisiana Retail Meats

Abstract: We investigated the prevalence of Staphylococcus aureus and methicillin-resistant S. aureus (MRSA) in 120 retail meat samples from 30 grocery stores in Baton Rouge, LA. S. aureus strains were recovered from 45.6% of pork samples and 20% of beef samples, whereas MRSA strains were isolated from six meat samples (five pork samples and one beef sample). The MRSA isolates were of two strain types (clones), one harboring Panton-Valentine leucocidin and belonging to pulsed-field gel electrophoresis type USA300 and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
138
11
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(173 citation statements)
references
References 22 publications
22
138
11
2
Order By: Relevance
“…MRSA wurde auch in Lebensmitteln in den Niederlanden, den USA und Kanada nachgewiesen [234][235][236]. Diese Nachweise erfolgten alle aus einer Anreicherungskultur heraus.…”
Section: Kastenunclassified
“…MRSA wurde auch in Lebensmitteln in den Niederlanden, den USA und Kanada nachgewiesen [234][235][236]. Diese Nachweise erfolgten alle aus einer Anreicherungskultur heraus.…”
Section: Kastenunclassified
“…The isolation of MRSA from different meat samples was reported previously from different countries (16)(17)(18)(19)(20)(21)(22)(23). Another study (10) reported MRSA strains from poultries in Iran; therefore, the isolation of MRSA strains from chicken meat was not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, the Federal Institute for Risk Assessment reported a contamination rate of 32% in turkey meat in Berlin, Germany [126]. Similar contamination frequencies were reported from Canada and the USA [72,127], as well as from Taiwan [128]. Moon et al [91] reported that the S. aureus isolated from chicken carcasses contained 1.3% MRSA, which was more than the MRSA isolated from other animal carcasses (0.3%) in Korea.…”
Section: Poultry Mrsamentioning
confidence: 64%
“…A USA survey of 120 retail meat samples indicated that 39.2% contained S. aureus strains, 5% of which were MRSA of the types USA100 (ST5) and USA300 (ST8) [127]. A Canadian survey [72] found that 7.7% of retail meat samples harbored MRSA; 30% belonged to the clonal complex CC398, 40% were CC8, and 30% were CC5, a strain commonly found in humans in both the USA and Canada.…”
Section: Frontiers In Staphylococcus Aureus 52 Frontiers In Staphylocmentioning
confidence: 99%